2020
DOI: 10.1177/0009922820910823
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Care Coordination and Preventive Care Among Children With Special Health Care Needs

Abstract: Care coordination (CC) has shown positive outcomes among children with special health care needs (CSHCN); however, the association between CC and well-child care (WCC) visits is unknown. We hypothesize that CSHCN who receive CC are more likely to attend the recommended WCC visits. A retrospective cohort analysis was conducted of patients aged 15 months attending the Arizona Children’s Center clinic. Logistic regression models explored the association between children receiving CC and attending the recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Missing these recommended care considerations could lead to complications from co-occurring conditions, as well as gaps in care [ 7 , 8 ]. Further, it has been found that successful implementation of care coordination can increase completion of well-child care [ 9 ]. Care coordination can also influence caregivers’ perceptions of how well the care provided meets the needs of their families [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Missing these recommended care considerations could lead to complications from co-occurring conditions, as well as gaps in care [ 7 , 8 ]. Further, it has been found that successful implementation of care coordination can increase completion of well-child care [ 9 ]. Care coordination can also influence caregivers’ perceptions of how well the care provided meets the needs of their families [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%